Multivariate Common Language Effect Size. (January 2015) - Liu, Xiaofeng Steven
To find a common language effect size of multivariate outcomes, we convert the standardized multivariate effect size (Mahalanobis distance) to a probability of a randomly selected subject from one population having a larger discriminant function than a randomly selected subject from another population. This probability is simple to calculate and comprehensible to laypeople. It can serve as the multivariate common language effect size to compare not only two groups but also more than two groups.